Specification for copper alloy pipe fittings for use with screwed copper tubes (BSI, 1970)
Pipe fittings, Copper alloys, Castings, Screwed fittings, Copper, Pipes, Marking, Dimensions, Pressure testing, Testing conditions, Threaded components, Elbows (pipes), Pipe tees, Pipe crosses, Pipe couplings, Pipe junctions, Bend couplings, Reducing couplings, Nipples (pipes), Size, Unions, Design, Nuts